Audio Description Made to Measure: Reflections on Interpretation in AD Based on the Pear Tree Project Data - Mazur, Iwona; Chmiel, Agnieszka (Rodopi, 2012)
The issue of interpretation in audio description continues to divide both AD practitioners and researchers. In this contribution we look at interpretation from the point of view of narratological behaviour of sighted viewers. To this end, we analyse data from twelve languages collected in the Pear Tree Project – a research project in which sighted viewers were asked to watch a short film and subsequently recount what they saw. Linking our findings to AD, we find in our analysis that sighted viewers interpret visual events but they avoid extremely subjective interpretations or interpretations in which they pass moral judgments. Thus, we propose that instead of applying the binary opposition of objective versus subjective, we should rather be using an objectivity– subjectivity scale, which can help determine which interpretive descriptions are less subjective and can consequently be used in AD without running the risk of being patronising or spoon-feeding the sense to the visually impaired.
Keywords: audio description; reception studies; interpretation; facial expressions; Pear Tree Project